2001
DOI: 10.1139/g01-064
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and ISSR fingerprints as useful genetic markers for analysis of genetic diversity, varietal identification, and phylogenetic relationships in peanut (Arachis hypogaea) cultivars and wild species

Abstract: Twenty-one random and 29 SSR primers were used to assess genetic variation and interrelationships among subspecies and botanical varieties of cultivated peanut, Arachis hypogaea (2n = 4x = 40), and phylogenetic relationships among cultivated peanut and wild species of the genus Arachis. In contrast with the previous generalization that peanut accessions lack genetic variation, both random and SSR primers revealed 42.7 and 54.4% polymorphism, respectively, among 220 and 124 genetic loci amplified from 13 access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
115
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 45 publications
9
115
0
8
Order By: Relevance
“…Por ejemplo, Chennaoui-Kourda et al (2007) utilizando marcadores ISSR en el análisis de la relación entre Sulla spinosissima y S. capitata, mostraron la existencia de una gran diferenciación genética entre estas dos especies; mientras que Shi et al (2006) en el análisis molecular de 20 especies de Lycoris, reconocieron cuatro grandes grupos de especies, lo que resultó congruente con sus observaciones morfológicas y citológicas. Resultados similares acerca de marcadores ISSR fueron encontrados en trigo, cebada, algodón y otras plantas (Chen et al 2007, Yockteng et al 2003, Xu & Sun 2001, Raina et al 2001, Hang et al 2003, Liu 1999. Así mismo Angiosperm Phylogeny Group (APG 2003), viene apoyando desde la década de los noventa el uso de marcadores moleculares en estudios filogenéticos de plantas, principalmente con la finalidad de proporcionar una nueva visión filogenética en la sistemática de plantas con flores.…”
Section: Introductionunclassified
“…Por ejemplo, Chennaoui-Kourda et al (2007) utilizando marcadores ISSR en el análisis de la relación entre Sulla spinosissima y S. capitata, mostraron la existencia de una gran diferenciación genética entre estas dos especies; mientras que Shi et al (2006) en el análisis molecular de 20 especies de Lycoris, reconocieron cuatro grandes grupos de especies, lo que resultó congruente con sus observaciones morfológicas y citológicas. Resultados similares acerca de marcadores ISSR fueron encontrados en trigo, cebada, algodón y otras plantas (Chen et al 2007, Yockteng et al 2003, Xu & Sun 2001, Raina et al 2001, Hang et al 2003, Liu 1999. Así mismo Angiosperm Phylogeny Group (APG 2003), viene apoyando desde la década de los noventa el uso de marcadores moleculares en estudios filogenéticos de plantas, principalmente con la finalidad de proporcionar una nueva visión filogenética en la sistemática de plantas con flores.…”
Section: Introductionunclassified
“…Raina et al (2001) Entre os 26 acessos no grupo II, 12 distribuídos em três sub-grupos geneticamente distintos apresentaram, dentro de cada grupo, 100% de similaridade, o que mostra que embora um elevado número de iniciadores tenha sido utilizado, esses acessos não puderam ser diferenciados. Os dados do presente trabalho estão de acordo com os apresentados na literatura, que mostram polimorfismo baixo para a espécie Arachis hypogaea, mesmo quando se utilizam marcadores considerados mais informativos (Hopkins et al, 1999;He et al, 2003He et al, , 2005Ferguson et al, 2004;Moretzsohn et al, 2004Moretzsohn et al, , 2005.…”
Section: Resultsunclassified
“…Para superar essas limitações, alguns autores aumentaram o número de iniciadores utilizados (Dwivedi et al, 2001;Raina et al, 2001), analisaram acessos de diferentes variedades botânicas (Subramanian et al, 2000;Raina et al, 2001) e, mais recentemente, iniciadores microssatélites têm sido desenvolvidos e utilizados em estudos de diversidade genética, em várias espécies do gênero Arachis (Hopkins et al, 1999;He et al, 2003He et al, , 2005Ferguson et al, 2004;Moretzsohn et al, 2004Moretzsohn et al, , 2005Palmieri et al, 2005;Bravo et al, 2006;Hoshino et al, 2006 …”
Section: Resultsunclassified
See 1 more Smart Citation
“…The utility of molecular markers are generally determined by the technology that is used to reveal DNA-based polymorphisms. Recent studies have shown that simple sequence repeats (SSRs) and random amplified polymorphic DNA (RAPDs) are able to detect a certain degree of polymorphism in different plant species (He and Prakash 1997, He et al 2003, Hopkins et al 1999, Subramanian et al 2000, Raina et al 2001.…”
mentioning
confidence: 99%